Cell Patterning: Patterned Three‐Dimensional Encapsulation of Embryonic Stem Cells using Dielectrophoresis and Stereolithography (Adv. Healthcare Mater. 3/2013). Issue 3 (6th March 2013) - Bajaj, Piyush; Marchwiany, Daniel; Duarte, Carlos; Bashir, Rashid
<x xml:space="preserve">Abstract</x> The integration of dielectrophoresis (DEP) with stereolithography (SL) apparatus for the spatial patterning of cells on custom‐made gold micro‐electrodes is reported by Rashid Bashir and co‐workers on page 450. After patterning, the cells are encapsulated in poly (ethylene glycol) diacrylate (PEGDA) hydrogels of different stiffnesses. This robust and flexible in vitro platform can enable various applications in stem cell differentiation and tissue engineering by mimicking elements of the native 3D in vivo cellular micro‐environment. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>